Pengaruh Motivasi Kerja dan Keselamatan Kerja Terhadap Kepuasan Kerja Karyawan Bagian Operator PT. XYZ - Adiwijaya, Dessy Fitria Kurniadi; Mulyana, Aam Rachmat (Jurnal EMT KITA, 2025)
Employee job satisfaction has a positive effect on both companies and organizations. Improving job satisfaction can be achieved by observing employee work motivation and workplace safety. Based on turnover data from the operators at PT. XYZ, which stands at 8.5%, exceeds the company's minimum policy of 5%. This study aims to determine the relationship between work motivation, workplace safety, and job satisfaction among operators at PT. XYZ. The research method used is quantitative, with the sampling technique being saturated sampling. The population for this study consists of 48 individuals. Data collection techniques include distributing questionnaires and conducting interviews. Data analysis techniques employ descriptive and associative methods, with multiple regression analysis using SPSS version 25 output tables. The results indicate that work motivation has a partial effect on job satisfaction, and workplace safety also has a partial impact on job satisfaction. Furthermore, work motivation and workplace safety simultaneously influence the job satisfaction of operators at PT. XYZ.
Keywords: Work Motivation; Work Safety; Job Satisfaction